National counter-terrorism strategies : legal, institutional, and public policy dimensions in the US, UK, France, Turkey, and Russia - NATO Advanced Research Workshop on National Counter-Terrorism Strategies : Legal, Institutional and Public Policy Dimensions in the US, UK, France, Turkey and Russia (2006 : Washington, D. C.); Orttung, Robert W.; Makarychev, A. S. (Andrei Stanislavovich); North Atlantic Treaty Organization (Amsterdam : IOS Press, 2006)
01